Redefine the Role of Spot-Scanning Proton Beam Therapy for the Single Brain Metastasis Stereotactic Radiosurgery - Chang, Sheng; Liu, Gang; Zhao, Lewei; Zheng, Weili; Yan, Di; Chen, Peter; Li, Xiangpan; Yang, Kunyu; Deraniyagala, Rohan; Stevens, Craig; Grills, Inga; Chinnaiyan, Prakash; et al. (Frontiers in Oncology, 2022)
Purpose: To explore the role of using Pencil Beam Scanning (PBS) proton beam therapy in single lesion brain stereotactic radiosurgery (SRS), we developed and validated a dosimetric in silico model to assist in the selection of an optimal treatment approach among the conventional Intensity Modulated Proton Therapy (IMPT), Volumetric Modulated Arc Therapy (VMAT) and Spot-scanning Proton Arc (SPArc). Material and Methods: A patient’s head CT data set was used as an in silico model. A series of targets (volume range from 0.3 cc to 24.42 cc) were inserted in the deep central and peripheral region, simulating targets with different sizes and locations. Three planning groups: IMPT, VMAT, and SPArc were created for dosimetric comparison purposes, and a decision tree was built based on this in silico model. Nine patients with single brain metastases were retrospectively selected for validation. Normal tissue complication probability (NTCP) of brain radionecrosis (RN) was calculated using the Lyman-Kutcher-Burman (LKB) model, and total treatment delivery time was calculated. Six physicians participated in the blinded survey to evaluate the plan quality and rank their choices. Results: The study showed that SPArc has a dosimetric advantage in the V12Gy and R50 with target volumes > 9.00 cc compared to VMAT and IMPT. A significant clinical benefit could be found in deep centrally located large lesions larger than 20.00 cc using SPArc because of the superior dose conformity and mean dose reduction in healthy brain tissue. Additionally, SPArc significantly reduced the treatment delivery time compared to VMAT (SPArc 184.46 ± 59.51s vs. VMAT: 1574.78 ± 213.65s). Nine retrospective clinical cases and the blinded survey showed a good agreement with the in silico dosimetric model and decision tree. Conclusion: The study demonstrated the feasibility of using Proton beam therapy for single brain metastasis patients utilizing SPArc technique. The in silico dosimetric model and decision tree presented here could be used as a practical clinical decision tool to assist the selection of the optimal treatment modality among VMAT, IMPT, and SPArc.